1989
DOI: 10.3382/ps.0681447
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Selection for Increased Body Weight on the Incidence of Leiomyomas and Leiomyosarcomas in Japanese Quail

Abstract: Leiomyomas and leiomyosarcomas were observed in adult laying hens from lines of Japanese quail selected solely (HW) or partly (HW-HP; HW-LP) for increased 4-wk BW and the corresponding randombred control (R1). No neoplasms were observed in a line (LW) selected for decreased 4-wk BW based on observations in one generation. Line R1 served as the base population for Lines HW and LW and was maintained without conscious selection for any trait, Lines HW-HP and HW-LP were sublines of Line HW in which the males were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 20 publications
(18 reference statements)
1
7
0
Order By: Relevance
“…Myomas respond to the gonadal steroids estrogen and progesterone, and their epidemiology parallels the ontogeny and life-cycle changes in reproductive hormones. Smooth muscle tumors are also among the most common neoplasm in the avian species with prevalence varying up to 60% (3)(4)(5)(6)(7)(8)(9)(10)(11). Foster et al (10) reported that frequency of neoplasm ranged from 38.7% to 80% particularly in the quails.…”
Section: Introductionmentioning
confidence: 97%
“…Myomas respond to the gonadal steroids estrogen and progesterone, and their epidemiology parallels the ontogeny and life-cycle changes in reproductive hormones. Smooth muscle tumors are also among the most common neoplasm in the avian species with prevalence varying up to 60% (3)(4)(5)(6)(7)(8)(9)(10)(11). Foster et al (10) reported that frequency of neoplasm ranged from 38.7% to 80% particularly in the quails.…”
Section: Introductionmentioning
confidence: 97%
“…7,8 The predilection site for avian smooth muscle tumors is the genital system, especially the mesosalpinx of females and the epididymis and ductus deferens of males. 9 Leiomyosarcomas have been documented in pigeons (Columba livia), 10,11 budgerigars (Melopsittacus undulatus), 12,13 broiler chickens, 8,14 commercial layer flocks, 15 Japanese quail (Coturnix japonica), 16,17 golden pheasants (Chrysolophus pictus), 18 a blue-fronted Amazon parrot (Amazona aestiva), 19 and a sarus crane (Grus antigone). 20 In some reports, the metastatic and nonmetastatic neoplasms were associated with the avian leukosis/ sarcoma complex.…”
Section: Discussionmentioning
confidence: 99%
“…Leiomyomas of the reproductive tract occur in several species of domestic animals, including the potbellied pig [49], the quail [50], and the German Shepherd dog [51], and nondomestic animals such as the otter [52], seal [53], cheetah [54], white rhinoceros [55], elephant [56], and crab-eating macaque [57]. Although the high incidence of uterine fibroids and their associated clinical problems are significantly important among reproductive aged women, the molecular basis for the initial myocyte transformation and growth of these tumors remains unknown.…”
Section: Discussionmentioning
confidence: 99%